Pengembangan Karir Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening - CAHYAWATI SETIYANINGRUM, ANIZAH (Jurnal Ilmu Manajemen (JIM), 2019)
This research aims to determine and analyze the effect career development on employee perfomance trough job satisfaction as an intevening variable in PT PLN (Persero) Unit Induk Distribusi Jawa Timur UP3 Ponorogo.This research is a type quantitative research with population is permanent employes in PT PLN (Persero) Unit Induk Distribusi Jawa Timur UP3 Ponorogo and tehnique sampling with a sample saturated with sample of 63 employees. Statistical analysis used in this research is Partial Least Square (PLS) with software SmartPLS 3. This results of this research show that career development has no significant and positive effect on employee performance, career development has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance. Job satisfaction mediates the effect of career development on employee performance. Keywords: career development; employee perfomance; job satisfaction